Sensory recovery of myomucosal flap oral cavity reconstructions. Issue 3 (11th November 2017) - Massarelli, Olindo; Vaira, Luigi Angelo; Biglio, Andrea; Gobbi, Roberta; Dell'aversana Orabona, Giovanni; De Riu, Giacomo
Abstract: Background: Sensory restoration of the oral cavity is a primary aim of reconstructive surgery in posttraumatic or postablative defects. Sensitivity plays a key role in oral function, whose impairment strongly affects the patient's quality of life. Cheek myomucosal flaps provide a reliable and tissue‐like reconstruction of these regions but their sensitive recovery, which we still know little about, deserves thorough assessment. Methods: In this retrospective study, the myomucosal cheek flaps were tested for different aspects of sensory recovery: touch; 2‐point discrimination; pain; sharp/smooth discrimination; ability to feel hot/cold stimulus; stereognosis; and taste. Results: Fifty‐two myomucosal flap reconstructions were investigated. All sensitivity tests showed positive results. When comparison was possible, sensitivity seemed significantly close to the contralateral healthy side. Sensory recovery proved to be even better than that reported on reinnervated microvascular free flap reconstructions of the oral cavity. Conclusion: Myomucosal flap reconstruction demonstrated a high degree of sensory recovery.